2014
DOI: 10.3991/ijac.v7i3.4020
|View full text |Cite
|
Sign up to set email alerts
|

E-learning Readiness and Absorptive Capacity in the Manufacturing Industry

Abstract: Abstract-The manufacturing industry constantly strives to develop the competencies of their expert production engineers in order to achieve and maintain a competetive advantage. Research shows that the absorptive capacity of a firm is central in order to reach such a goal. The absorptive capacity is the firm´s ability to recognize the value of new external information, assimilate it, and apply it to commercial ends, and thereby exploit the conditions for innovation. In this paper the concept of absorptive capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Only two global companies had strategies for strategic collaboration outside their own company. High e-learning readiness and absorptive capacity are two concepts that comprise the capabilities that organizations' need in order to capitalize on e-learning initiatives [48].…”
Section: Initiation Phasementioning
confidence: 99%
“…Only two global companies had strategies for strategic collaboration outside their own company. High e-learning readiness and absorptive capacity are two concepts that comprise the capabilities that organizations' need in order to capitalize on e-learning initiatives [48].…”
Section: Initiation Phasementioning
confidence: 99%
“…The study reported here stems from an initiative of addressing the challenge of meeting industrial competence needs, in Swedish manufacturing industry, in an era of digital transformation. The participating university has a long tradition of close collaboration with industry via research and education, and approaches for co-production have evolved over time (Gustavsson 2018;Hattinger et al 2014;Hattinger and Eriksson 2020). We apply our understanding of the manufacturing industry's specific competence needs to develop courses suitable for professionals working full time.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier leaders/managers need to create a favourable learning environment to facilitate organisational innovation and creativity. Learning is defined as the change in individual behaviour due to experiences based on actions and events (Hattinger, Eriksson, Malmsk€ old, & Svensson, 2014) or information and knowledge (Odirile, Mpofu, & Montsi, 2009). Edmondson (1999) defined organisational learning as an ongoing process of reflection and action, characterised by asking questions, seeking feedback, experimenting, reflecting on results, and discussing errors or unexpected outcomes of actions.…”
Section: Introductionmentioning
confidence: 99%